Introduction of federal state educational standards of higher education: the first year of work in estimations and opinions of experts - S. V. Korshunov; V. V. Zyryanov (Moscow Polytechnic University, 2022)
The article continues to present the results of monitoring the implementing effectiveness of the Federal State Educational Standards conducted by the Association of Classical Universities of Russia, Association of Technical Universities and the Comprehensive Research Institute of Education MSU in late 2011 - the beginning of 2012. The article provides the data obtained in the course of direct interviewing the teaching faculty employees who are responsible for the introduction of the FSES in the structural units of the university. Interviewing has been carried out according to the scenario, which included twelve questions covering the main aspects characterizing the preparedness of educational process participants to work in accordance with FSES of higher education.